Mengembangkan Active Learning melalui Amplop Pintar: Integrasi Card Sort dan Educational Games dalam Pembelajaran Pendidikan Agama Islam di Sekolah Menengah Kejuruan - Aisyah Puan Maharani; Sunhaji; Nurkholis; Fajry Sub’haan Syah Sinaga (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2025)
Active learning strategies are increasingly important for fostering student engagement and participation, with educational games serving as effective teaching tools. By presenting content interactively, these games enhance comprehension and create a stimulating play-based environment that supports meaningful learning outcomes. This study explores the use of educational games in teaching Islamic Religious Education at SMK Negeri 1 Purwokerto, using a descriptive qualitative design. Data were collected from teachers and 10th grade PPLG students through observation, interviews, and documentation. The analysis included data reduction, presentation, and conclusion drawing, with validity ensured through triangulation. The findings show that active learning through educational games was effectively applied and aligned with current pedagogical principles. Teachers increased student engagement with activities such as the Amplop Pintar or Smart Envelope game, which successfully combined enjoyment with deeper learning.